Impact of Microsetella norvegica on carbon flux attenuation and as a secondary producer during the polar night in the subarctic Porsangerfjord - Mooney, Benjamin Paul; Iversen, Morten Hvitfeldt; Norrbin, Maria Fredrika (Frontiers in Marine Science, 2023)
We investigated the role of Microsetella norvegica, a small harpacticoid copepod, for particulate organic 21 carbon flux attenuation via aggregate feeding in a subarctic fjord. We quantified the vertical distribution 22 and abundance of M. norvegica, phytoplankton, and marine snow simultaneously with a Digital 23 Autonomous Video Plankton Recorder in Porsangerfjord, northern Norway, between August 2013 and 24 November 2014. We estimated the highest abundance of M. norvegica as 4.86x106 individuals m-2 in 25 October. We propose that M. norvegica preferred diatoms over both marine snow and the prymnesiophyte 26 Phaeocystis pouchetii during euphotic bloom conditions. However, during oligotrophic conditions when 27 phytoplankton were scarce, M. norvegica switched to marine snow as a food source. M. norvegica has the 28 potential to explain 1.4% and 0.29% of the total carbon flux attenuation in October and November, 29 respectively. These results suggest that small copepods feed on settling detritus when no alternative food 30 is available. Detritus feeding by M. norvegica may have an ecological impact during the polar night, both 31 via direct carbon flux attenuation, but also as secondary producers in periods with low primary production. 32 Currently small copepods such as M. norvegica are not included in carbon budgets or large-scale 33 modelling, but considering their potentially high abundance they may represent an important but 34 overlooked pathway in both the carbon cycle and trophic level interactions.